Bis(perchlorocatecholato)silane - a neutral silicon Lewis super acid - Maskey, Rezisha; Schädler, Marcel; Legler, Claudia; Greb, Lutz (Angewandte Chemie. International edition, 2018)
No neutral silicon Lewis super acids are known to date. We report on the synthesis of bis(perchlorocatecholato)silane and verify its Lewis super acidity by computation (DLPNO-CCSD(T)) and experiment (fluoride abstraction from SbF6−). The exceptional affinity towards donors is further demonstrated by, for example, the characterization of an unprecedented SiO4F2 dianion and applied in the first hydrodefluorination reaction catalyzed by a neutral silicon Lewis acid. Given the strength and convenient access to this new Lewis acid, versatile applications might be foreseen.
First published: 14 December 2017
Gesehen am 15.10.2019